Conservation Strategy for Endangered Medicinal Plant - Black Turmeric (Curcuma caesia) - Chitra, R.; Janaki, D.; Jansirani, P. (Indian Forester, 2022)
Black turmeric (Curcuma caesia Roxb.) is commonly known as kali haldi and it belongs to the family Zingiberaceae. The plant has a characteristic rhizome flesh of bluish-black colour with pungent smell and hot bitter taste. The crop is gaining popularity in nowadays due to its anticancerous property and short supply from the traditional forest areas. It is widely used as an important medicine to cure cancer in Chinese medicine. Its availability in forest area has continuously declined and the species needs to be restoring in non-conventional forest areas especially on farmer’s field. It is propagated through rhizomes and large quantity of rhizome is required because of its poor vegetative propagation efficiency. Rhizomes are susceptible to diseases that cause tissue senescence and degeneration during storage and cultivation. It is difficult to propagate through seed because of poor flowering and inability to seed set. The planting material is not chiefly available for commercial cultivation. To overcome this problem, planting material produced from single bud rhizome of black turmeric under shade net condition will be planted instead of rhizomes. The main objective of this paper is to standardize the growing media for mass multiplication of black turmeric. Among the various treatments, rhizome with single bud planted in a growing media of cocopeat + vermicompost + Pseudomonas flouorescence give better crop establishment (95.99 per cent). Hence, rapid multiplication of black turmeric through single bud rhizome has been considered as the conservation strategy for this endangered medicinal plant.